Echocardiographic Evaluation of Pericardial Effusion and Cardiac Tamponade - Pérez-Casares, Alejandro; Cesar, Sergi; Brunet-Garcia, Laia; Sanchez-de-Toledo, Joan (Frontiers in Pediatrics, 2017)
Pericardial effusion is defined by an increase in the physiological amount of fluid within the pericardial space. It can appear following different medical conditions, mainly related to inflammation and cardiac surgery. Cardiac tamponade is a critical condition that occurs after sudden and/or excessive accumulation of fluid in the pericardial space that restricts appropriate filling of the cardiac chambers disturbing normal hemodynamics and ultimately causing hypotension and cardiac arrest. It is; therefor, a life-threatening condition that must be diagnosed as soon as possible for correct treatment and management. Echocardiographic evaluation of pericardial effusion is paramount for timely and appropriate diagnosis and management. A structured echocardiographic approach including two-dimensional, M-mode and Doppler echocardiographic evaluation assessing: i) quantity and quality of pericardial fluid, ii) collapse of cardiac chambers, iii) respiratory variation of the ventricular diameters, iv) inferior vena cava collapsibility and iv) flow patterns in atrioventricular valves should give the bedside clinician the necessary information to appropriately manage pericardial effusion. Here, we review these key echocardiographic signs that will ensure an appropriate assessment of a patient with pericardial effusion and/or cardiac tamponade.